High‐Performance Lead‐Free Piezoceramics with High Curie Temperatures. (7th October 2015) - Lee, Myang Hwan; Kim, Da Jeong; Park, Jin Su; Kim, Sang Wook; Song, Tae Kwon; Kim, Myong‐Ho; Kim, Won‐Jeong; Do, Dalhyun; Jeong, Il‐Kyoung
Abstract : A bismuth ferrite and barium titanate solid solution compound can achieve good piezoelectric properties with a high Curie temperature when fabricated with low‐temperature sintering followed by a water‐quenching process, with no complicated grain alignment processes performed. By adding the super‐tetragonal bismuth gallium oxide to the compound, the piezoelectric properties are as good as those of lead zirconate titanate ceramics.